Predictors and time to poor management outcomes among pediatric patients hospitalized with pneumonia in the Gedeo Zone, southern Ethiopia: a prospective follow-up study - Alemu, Wagaye; Ademassu, Mebirat; Belayneh, Firehiwot; Gebeyehu, Yabibal; Zenebe, Getachew Assefa; Lerango, Temesgen Leka (Frontiers in Pediatrics, 2025)
BackgroundPneumonia and other lower respiratory tract infections are the leading causes of death worldwide. Accurate diagnosis, identification of complications and underlying conditions, and appropriate treatment are essential for preventing pneumonia-related morbidity and mortality. Children in developing countries, such as Ethiopia, are at risk of contracting pneumonia, which could lead to death if not treated correctly. Therefore, we sought to assess the predictors and time to management outcomes among pediatric patients hospitalized with pneumonia in the Gedeo Zone, southern Ethiopia.MethodsA multicenter, institution-based prospective follow-up study was conducted among 484 pediatric patients hospitalized with pneumonia in the Gedeo Zone, southern Ethiopia. The data were entered into EpiInfo version 7 and exported to STATA version 15 for analysis. Survival analysis using a Cox proportional hazards model was performed to identify predictors of poor management outcomes. Associations between predictors and poor management outcomes were estimated using a p-value <0.05 and adjusted hazards ratios (AHR) with 95% CIs.ResultsAmong the 484 patients admitted with pneumonia, 381 (78.7%) recovered, 16 (3.3%) died, 6 (1.2%) were transferred out, and 81 (16.7%), defaulted. Over the study period, the incidence rate of poor management outcomes was 4 per 100 person-days of observation, while the incidence rate of recovery was 15 per 100 person-days of observation. According to the multivariable Cox regression analysis, the factors significantly associated with poor management outcomes were comorbidities at admission (AHR = 2.27, 95% CI: 1.01–5.26), age (AHR = 5.96, 95% CI: 2.71–13.1), nutritional status (AHR = 1.54, 95% CI: 1.08–3.17), and residence (AHR = 1.58, 95% CI: 1.05–2.34).ConclusionThe incidence rate of poor management outcomes was 4 per 100 person-days of observation. Comorbidities at admission, age, nutritional status, and place of residence were statistically significant predictors of poor management outcomes.